The effect of compatibilizer and coupling agent on properties and characterization of ethylene vinyl acetate / natural rubber / potash feldspar composites / Ho Shuh Huey - Ho, Shuh Huey (School of Material Engineering, Universiti Malaysia Perlis, 2017)
This research concentrats on the effect of compatibilizers and chemical modifications of PF on the mechanical, swelling behaviour, morphological and thermal properties of EVA/NR/PF composites. The objectives of this research are ; to study the effect of various compatibilizers (polyethylene- grafted-maleic anhydride, isophathalic acid-maleic anhydride, ethylene vinyl acetate- grafted- phthalic anhydride and ethylene vinyl acetate- grafted- benzyl urea) on properties of EVA/NR/PF composites ; to analyse the effect of chemical modification of potash feldspar with silane coupling agent and glycolic acid- maleic anhydride (GA-MA) on properties of EVA/NR/PF composites ; to compare the effect of compatibilizer (ethylene vinyl acetate- grafted- benzyl urea) and glycolic acid/ maleic anhydride on properties of ethylene vinyl acetate/ natural rubber/ potash feldspar (EVA/NR/PF) compositesat 5, 15 and 25 phr of PF loading.